ISLAMIC STUDENT EMPOWERMENT HEALTHY PROGRAM - Sari, Dian C; Kartini, Sri; Suwignyo, Suwignyo; Isnainin, Lailatul (Jurnal Pengabdian Masyarakat Multidisiplin, 2018)
The 2016 Population Census results show that Indonesia's population is 237.6 million, 63.4 million of which are teenagers consisting of 32,164,436 men (50.70 percent) and 31,279,012 women (49 , 30 percent). The size of the population of the youth group will greatly affect population growth in the future. With the rapid development of technology, the development of teenagers in Indonesia is also developing. Some lead to positive and negative things. One of the negative impacts is the lack of awareness about the STBM pillars. Community-Based Total Sanitation (STBM) is an integrated action to reduce the incidence of environmental-based infectious diseases, as well as improve hygiene behavior and the quality of life of Indonesian people. Uniqueness / Excellence Islamic healthy student empowerment program lies in the variation and composition of the dedication material. The specifications that will be produced are that the program that will be implemented is one of the main keys to improving the program of healthy students. This service aims to show that schools have a positive impact on supporting health programs for students so that schools have an important role in promoting and intervening in the development of student health. The development of student health that is supported by the school is an important factor in the phase of forming a superior generation of the nation's future. This service program is carried out on students of SMA 1 Perhentian Raja and SMKN 2 pekanbaru.